Healthcare Providers’ Oral Health Practices Participating in a Regional Oral Health Intervention - Patricia A. Braun; Kimberly T. Wiggins; Cherith Flowerday; Andrew Bienstock; L. Miriam Dickinson (Journal of Primary Care & Community Health, 2025)
Objective: Evaluate healthcare providers’ and staffs’ knowledge, self-reported abilities, activities, and barriers to providing preventive oral health services (POHS) at primary care medical visits before and after participation in the Rocky Mountain Network of Oral Health (RoMoNOH) project. Methods: The RoMoNOH project integrated POHS into primary care medical visits of young children at 22 community health centers (CHCs) in Arizona, Colorado, Montana, and Wyoming by medical team members and/or by embedded dental hygienists (DHs). Twelve CHCs embedded DHs onto their teams. In an observational pre/post evaluation, a convenience sample of healthcare providers’ characteristics were surveyed at baseline and 3 years across 4 oral health domains: knowledge, self-reported abilities, behaviors, and barriers. Each domain was scored from 0% to 100%, with 100% being optimal. Differences between pre- and post-project domain scores were assessed using chi-square, t-tests, and linear and logistic regression adjusting for providers’ age. Results: Embedding DHs into CHCs and staff turnover impacted pre/post survey participants. The final analytic cohort included 213 (pre-survey response rate: 71%) and 165 (post-survey response rate: 52%) healthcare providers who worked with children < age 3. Participants were female (pre: 81%, post: 81%) and aged >35 years (pre: 39%, post: 41%). Unadjusted mean differences across surveys improved across all oral health domains (pre/post): knowledge: 65%/81%, P  < .001; self-reported ability: 52%/71%, P  < .001; activities: 32%/57%, P  < .001; barriers: 27%/21%, P  = .011. After adjustment for age, these improvements remained significant (all P  ≤ .011). Conclusions: Healthcare providers’ oral health practices improved over a multi-year oral health integration project aimed at increasing delivery of POHS at medical visits.